ANALISIS PENGARUH LEMBAGA KEUANGAN MIKRO DAN INDEKS PEMBANGUNAN MANUSIA TERHADAP KETIMPANGAN PENDAPATAN DI INDONESIA - Prasetya, Maria Agape Widya; Lutfitasari, Princisca; Sairo, Justi; Saraswati, Birgitta Dian (FACULTY OF ECONOMICS AND BUSINESS FLORES UNIVERSITY, 2022)
Income inequality is still a problem in the Indonesian economy. In order to realize the welfare of the people evenly, the government seeks to reduce the income inequality between provinces in Indonesia. The existence of microfinance institutions (MFIs) is expected to help the economy of the poor so that income distribution will be realized. This study aims to analyze the effect of loans disbursed by MFIs, the number of MFIs and the human development index (HDI) on income inequality in Indonesia. By using panel data regression analysis with a fixed effect model approach, this study shows that the number of loans disbursed techniques by MFIs has a significant positive effect on income inequality in Indonesia, while the HDI variable and the number of MFIs have no effect on income inequality in Indonesia